Caregivers Like Me: An Education Intervention for Family Caregivers of Latino Elders at End-of-Life - Cruz-Oliver, Dulce M. (MedEdPORTAL, 2016)
INTRODUCTION: End-of-life (EOL) care delivery to Latinos is a well-documented challenge. The majority of caregivers for Latino patients are family relatives, but because Latino caregivers may spend more hours in the caregiving role than other ethnic groups and are less likely to use additional available health care, caregivers can experience an increased burden. This can result in Latino elders being more vulnerable to receiving aggressive care. “Caregivers Like Me” was created as a source for nonprofessional caregivers to improve their knowledge about Latino caregiving of elders at end-of-life (EOL). This resource aims to educate about caregiver stress and to improve attitudes towards the utilization of EOL services. METHODS: “Caregivers Like Me” is a bilingual education intervention that includes a video soap opera, or telenovela. The video is followed by discussion of hospice, palliative care, and caregiver stress definitions and ends with an explanation of services available for caregivers (i.e., social services, support groups, adult day care, chore workers, home care with or without palliative care, and respite care under hospice). RESULTS: “Caregivers Like Me” has been demonstrated to improve Latino family caregivers’ openness to receiving professional help while caring for their loved ones. Participants in a multisite cross-sectional pilot study among nonprofessional Latino caregivers (N = 145) reported active learning from the intervention and high satisfaction with the overall educational experience. DISCUSSION: This tool provides an education format that is culturally and literacy-sensitive to Latino caregivers and effective in changing their attitude toward EOL care. It may be used by professional caregivers to educate Latino caregivers about EOL care.